Emergence of heartbeat frailty in advanced age II: individual cardiovascular aging trajectories revealed by lifelong echocardiography in male mice - Ismayil Ahmet; Nolan M. Winicki; Jacob S. Roberts; Christopher H. Morrell; Edward G. Lakatta (GeroScience, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Identification of Genetic Variation Associated With Heat Tolerance in Cowpea ( Vigna unguiculata L. Walp.) - Roland Akakpo; Elaine J. Lee; Jacob B. Pacheco; Esteban F. Rios; Michael B. Kantar; Ousmane Boukar; Kevin M. Volz; Habib Akinmade; Luis Getino; Kenneth J. Boote; María Muñoz‐Amatriaín; Peter L. Morrell (Molecular Ecology, 2026)
Heat tolerance is an important trait in cowpea, a crop that is the primary protein source for a large portion of the human population in sub‐Saharan Africa. Cultivated, landrace, semi‐wild, and wild cowpea grow across the region in diverse climatic conditions. This study used environmental association (envGWAS) and allele‐frequency outlier approaches across a panel of 580 gene bank accessions to identify genomic regions associated with adaptation to heat and limited precipitation. Allele frequency outliers are detected independent of potential selective factors driving differentiation; we used a ranking‐based approach to identify the climate variables most associated with variants among outliers. Precipitation‐related variables dominated the signals we identified for envGWAS and allele frequency outliers. We identified variants on all 11 chromosomes that are putatively associated with cowpea adaptation to higher‐temperature environments. The overlap between variants associated with low precipitation and high temperature suggests that these traits may be inextricably linked in cowpea. The Sahel region is the source of many accessions with derived variants associated with high temperatures, suggesting that accessions from this region could contribute heat tolerance alleles for cowpea improvement.

Comparison of cryoprotectant agents and their concentrations on the post-thaw quality of alpaca (Vicugna pacos) epididymal spermatozoa - Alexei Santiani; Martha Ugarelli; Luis Ruiz; Omar Quispicondor; Caroline Duymovich; Jane M. Morrell; Shirley Evangelista-Vargas (Cryobiology, 2025)

Controlling matric potential in microfluidics to examine microbial dynamics in unsaturated porous media - Shane M. Franklin; Scott T. Retterer; Amber N. Bible; Jennifer L. Morrell-Falvey (Soil Biology and Biochemistry, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Preparing boar semen using single layer centrifugation through low density Porcicoll does not negatively affect sperm viability - Ziyad Al-Kass; Mohua Dasgupta; Kristýna Petričáková; Theodoros Ntallaris; Anders Johannisson; Jane M. Morrell (Animal Reproduction Science, 2025)

Sow reproductive performance after artificial insemination with semen doses processed using Single Layer Centrifugation without antibiotic in the tropics - CongBang Ngo; Junpen Suwimonteerabutr; Jane M. Morrell; Padet Tummaruk (Animal Reproduction Science, 2025)

Mitochondrial bioenergetics analysis on SLC-selected boar spermatozoa during liquid storage - Estibaliz Lacalle; Beatrice Mislei; Cristina Algieri; Marcella Spinaci; Felipe Martinez Pastor; Salvatore Nesci; Jane M. Morrell; Jose M. Ortiz-Rodriguez; Diego Bucci (Animal Reproduction Science, 2025)

Bacterial survival below zero: Impact of storage time on bacterial viability in bull semen - Aleksandar Cojkic; Ingrid Hansson; Jane M. Morrell (Cryobiology, 2025)

Vestibular syndrome in dairy heifers associated with Mycobacterium bovis: two case reports and strain characterization - Germán J. Cantón; Yolanda M. Marron; María A. Fiorentino; Eleonora L. Morrell; Juan A. García; María J. Marfil; Facundo Urtizbiria; Claudia Morsella; Karina M. Cirone; María V. Scioli; Martín J. Zumárraga; Fernando Paolicchi (Veterinary Research Communications, 2025)

Protective effect of supplementation with water soluble β-carotene and α-tocopherol in boar sperm cooling-freezing extender, but not in the thawing extender - Adrián Martín-San Juan; Eduardo de Mercado; Helena Nieto-Cristóbal; Andrea Cabero; Miguel Ángel Silvestre; Jane M. Morrell; Manuel Álvarez-Rodríguez (Animal Reproduction Science, 2025)

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Boar semen microbiome: Insights and potential implications - CongBang Ngo; Jane M. Morrell; Padet Tummaruk (Animal Reproduction Science, 2025)

Use of a sperm-Hyaluronan binding assay for evaluation of sperm quality in dromedary camels - A. Kotila-Ioannou; JM Morrell; T. Ntallaris; M. Gargallo; J.A. Skidmore; C. Malo (Animal Reproduction Science, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sow reproductive performance following artificial insemination with semen doses processed using Single Layer Centrifugation without antibiotics in the tropics - CongBang Ngo; Junpen Suwimonteerabutr; Jane M. Morrell; Padet Tummaruk (Theriogenology, 2024)

Metagenomic identification of bull semen microbiota in different seasons - Aleksandar Cojkic; Adnan Niazi; Jane M. Morrell (Animal Reproduction Science, 2024)

A combination of biomarkers for predicting stallion sperm fertility - Anders Johannisson; Jane M. Morrell; Theodoros Ntallaris (Veterinary Research Communications, 2024)
Equine breeding would benefit greatly from reliable biomarkers of stallion or ejaculate fertility. The aim of the study was to investigate how several in vitro sperm characteristics correlate with fertility after artificial insemination, to explore the potential to build a fertility prediction model for stallions. Cooled insemination doses (3–5 per stallion) were obtained from various studs. Sperm membrane integrity, acrosome integrity, chromatin integrity, mitochondrial membrane potential, and reactive oxygen species production were evaluated by flow cytometry 24–30 h after semen collection, and sperm motility was assessed by computer aided sperm analysis. Calcein violet was used to differentiate viable spermatozoa. Per season pregnancy rates for these stallions were available the following year. Positive correlations were found between pregnancy rate and straightness (r = 0.43, p ≤ 0.001), as well as pregnancy rate and the proportion of living hydrogen peroxide positive spermatozoa (r = 0.32, p ≤ 0.05). There were negative correlations between pregnancy rate and amplitude of lateral head displacement (r = -0.26, p ≤ 0.05), and between pregnancy rate and the mean fluorescence of dead superoxide positive spermatozoa (r = -0.46, p < 0.001). Principal component analysis indicated that motility, membrane integrity, DNA fragmentation, and reactive oxygen species production were associated with pregnancy rate. Therefore, a combination of these factors could be used as a biomarker of fertility when assessing ejaculates. However, data from more individuals would be required to construct a model for fertility prediction.

Bacterial diversity in semen from stallions in three European countries evaluated by 16S sequencing - Pongpreecha Malaluang; Adnan Niazi; Yongzhi Guo; Christina Nagel; Tiago Guimaraes; Antonio Rocha; Christine Aurich; Jane M. Morrell (Veterinary Research Communications, 2024)
The microbiome plays a significant role in shaping the health and functioning of the systems it inhabits. The seminal microbiome of stallions has implications for the health of the reproductive tract, sperm quality during preservation and antibiotic use in semen extenders. Diverse bacteria are present on the external genital tract and a mix of commensal microorganisms populates various parts of the reproductive tract, influencing the seminal bacterial content. Other sources of bacteria include the environment, semen collection equipment, and personnel. The bacterial load can adversely affect sperm quality and fertility, particularly in artificial insemination, where semen is extended and stored before use. Antibiotics are frequently used to inhibit bacterial growth, but their effectiveness varies depending on the bacterial strains present. The aim of this study was to assess the bacterial diversity in semen from 37 healthy stallions across three European nations (Germany, Portugal, and Sweden) using 16S sequencing. Semen samples were collected from individual stallions at three AI centers; DNA extraction, sequencing, and bioinformatic analysis were performed. Differences in bacterial diversity among the stallions were seen; although bacterial phyla were shared across the regions, differences were observed at the genus level. Climate, husbandry practices, and individual variability likely contribute to these differences. These findings underscore the importance of tailoring antibiotic strategies for semen preservation based on regional bacterial profiles. The study presents a comprehensive approach to understanding the intricacies of the stallion seminal microbiome and its potential implications for reproductive technologies and animal health.

Enrichment of thawed boar spermatozoa with an intact membrane using Magnetic Activated Cell Sorting - Anders Johannisson; Jane M. Morrell; Margareta Wallgren (Animal Reproduction Science, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Effect of storage and single layer centrifugation before cryopreservation on stallion sperm cryosurvival - M.M. Nunes; J.M. Morrell; F.C.C. Santos; M.H. Miragaya; M.F. Gallelli; M. Rodriguez; J.D. Guimarães (Journal of Equine Veterinary Science, 2024)

Reduced bacterial load in stallion semen by modified single layer centrifugation or sperm washing - Pongpreecha Malaluang; Lisa Helène Wagner; Aleksandar Cojkic; Joachim Spergser; Christine Aurich; Jane M. Morrell (Theriogenology, 2024)

Single layer centrifugation as a method for bacterial reduction in bull semen for assisted reproduction - Aleksandar Cojkic; Ingrid Hansson; Anders Johannisson; Eva Axner; Jane M. Morrell (Veterinary Research Communications, 2024)
Semen samples contain bacteria originating from the animal urogenital tract, environment, and/or contamination during semen processing, negatively affecting sperm quality by producing toxins and/or competing for nutrients in extenders. The aims of this study were to evaluate two methods of Single-layer centrifuges (SLC), high and low density colloid, as a method for bacterial removal from bull semen, and to evaluate sperm quality after treatment. In total, semen samples from 20 bulls (3 ejaculates per bull) were used in this study. Bacterial reduction was evaluated by bacterial quantification (colony forming unit - CFU/mL) while bacterial identification was performed by matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) after culturing bacteria on blood agar. Sperm motility parameters were evaluated by Computer Assisted Sperm Analyses (CASA), and sperm chromatin structure assay (SCSA) by Flow cytometry. Both, High and Low density SLC reduced number of bacteria significantly (p < 0.001) compared with control. The difference in bacterial count between High and Low SLC was also significant (p < 0.001). Furthermore, High density SLC was successful in removing almost all Bacillus and Proteus spp. Most CASA parameters were significantly improved after both treatments (p < 0.001, p < 0.01, p < 0.05). The Deoxyribonucleic acid (DNA) fragmentation index evaluated by SCSA in High (p < 0.01) and Low (p < 0.05) SLC group differed significantly compared with control. Single-layer centrifugation (SLC) with either a high or a low density colloid is a suitable method for bacterial removal in bull semen.

Transplacental infection by bovine alphaherpesvirus type 1 induces protein expression of COX-2, iNOS and inflammatory cytokines in fetal lungs and placentas - Mercedes M. Burucúa; María A. Risalde; Felipe A. Cheuquepán; Silvina Quintana; Sandra E. Pérez; Germán J. Cantón; Dadin P. Moore; Anselmo C. Odeón; Irene Agulló-Ros; María Valeria Scioli; Claudio Barbeito; Eleonora L. Morrell; et al. (Veterinary Microbiology, 2023)

Barriers and Facilitators to a Healthy Community Environment During COVID-19: Perceptions of Extension Nutrition Educators and Other Key Community Stakeholders - E. Varela; J. Zeldman; A. Kuch; Y. Wang; M. Shushari; E. Hall; J. McNamara; J. Morrell; T. Tolar-Peterson; O. Brown; M. Olfert; L. Franzen-Castle; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Lessons learned in the practice of community-based participatory research with community partner collaboration in study design and implementation: the community scientist model - Megan A. Morrell; Tabitha R. Willis; Denisha R. Brown; Catherine A. O’Brian; Sharon L. Post; Gayle E. Woloschak; Marcelo G. Bonini; Tatjana Paunesku; Jelena Popovic; Tarneka M. Manning; Candace Henley; Jorge Girotti; et al. (Cancer Causes & Control, 2023)

Epididymal stallion sperm quality improves with single layer centrifugation prior to cryopreservation or post-thawing - Fernanda Carlini Cunha dos Santos; Jane M Morrell; Bruna da Rosa Curcio; Márcio Menezes Nunes; Eduardo Malschitzky (Journal of Equine Veterinary Science, 2023)

Colloid centrifugation as an alternative to antibiotics in stallion semen preparation - Pongpreecha Malaluang; Lisa Helène Wagner; Joachim Spergser; Christine Aurich; Jane M. Morrell (Journal of Equine Veterinary Science, 2023)

The relationship between sperm quality parameters and stallion fertility - Anders Johannisson; Aleksandar Cojkić; Jane M Morrell (Journal of Equine Veterinary Science, 2023)

Novel interpretation of sperm stress test and morphology for maturity assessment of young Norwegian Red bulls - Joanna Bremer; Bjørg Heringstad; Jane M. Morrell; Elisabeth Kommisrud (Animal Reproduction Science, 2023)

Single layer centrifugation (SLC) for bacterial removal with Porcicoll positively modifies chromatin structure in boar spermatozoa - Estíbaliz Lacalle; Estela Fernández-Alegre; Cristina Soriano-Úbeda; Sonia Martínez-Martínez; Juan Carlos Domínguez; J. Ramiro González-Montaña; Jane M. Morrell; Felipe Martínez-Pastor (Theriogenology, 2023)

Deciphering sperm chromatin properties to predict stallion sperm fertility - Ziyad Al-Kass; Theodoros Ntallaris; Jane M. Morrell; Anders Johannisson (Animal Reproduction Science, 2023)

Emergence of heartbeat frailty in advanced age I: perspectives from life-long EKG recordings in adult mice - Jack M. Moen; Christopher H. Morrell; Michael G. Matt; Ismayil Ahmet; Syevda Tagirova; Moran Davoodi; Michael Petr; Shaquille Charles; Rafael de Cabo; Yael Yaniv; Edward G. Lakatta (GeroScience, 2022)
The combined influences of sinoatrial nodal (SAN) pacemaker cell automaticity and its response to autonomic input determine the heart’s beating interval variability and mean beating rate. To determine the intrinsic SAN and autonomic signatures buried within EKG RR interval time series change in advanced age, we measured RR interval variability before and during double autonomic blockade at 3-month intervals from 6 months of age until the end of life in long-lived (those that achieved the total cohort median life span of 24 months and beyond) C57/BL6 mice. Prior to 21 months of age, time-dependent changes in intrinsic RR interval variability and mean RR interval were relatively minor. Between 21 and 30 months of age, however, marked changes emerged in intrinsic SAN RR interval variability signatures, pointing to a reduction in the kinetics of pacemaker clock mechanisms, leading to reduced synchronization of molecular functions within and among SAN cells. This loss of high-frequency signal processing within intrinsic SAN signatures resulted in a marked increase in the mean intrinsic RR interval. The impact of autonomic signatures on RR interval variability were net sympathetic and partially compensated for the reduced kinetics of the intrinsic SAN RR interval variability signatures, and partially, but not completely, shifted the EKG RR time series intervals to a more youthful pattern. Cross-sectional analyses of other subsets of C57/BL6 ages indicated that at or beyond the median life span of our longitudinal cohort, noncardiac, constitutional, whole-body frailty was increased, energetic efficiency was reduced, and the respiratory exchange ratio increased. We interpret the progressive reduction in kinetics in intrinsic SAN RR interval variability signatures in this context of whole-body frailty beyond 21 months of age to be a manifestation of “heartbeat frailty.”

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Spatial–temporal trends and economic losses associated with bovine abortifacients in central Argentina - Germán J. Cantón; Fabiana Moreno; María A. Fiorentino; Yanina P. Hecker; Maximiliano Spetter; Franco Fiorani; María G. Monterubbianesi; Juan A. García; Erika González Altamiranda; Karina M. Cirone; Enrique L. Louge Uriarte; Andrea E. Verna; et al. (Tropical Animal Health and Production, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Decreased mesolimbic dopaminergic signaling underlies the waning of maternal caregiving across the postpartum period in rats - Zachary A. Grieb; Erika M. Vitale; Joan I. Morrell; Joseph S. Lonstein; Mariana Pereira (Psychopharmacology, 2020)

Modification of plant cell wall chemistry impacts metabolome and microbiome composition in Populus PdKOR1 RNAi plants - Allison M. Veach; Daniel Yip; Nancy L. Engle; Zamin K. Yang; Amber Bible; Jennifer Morrell-Falvey; Timothy J. Tschaplinski; Udaya C. Kalluri; Christopher W. Schadt (Plant and Soil, 2018)

miR-451 limits CD4+ T cell proliferative responses to infection in mice - Lesley M. Chapman; Sara K. Ture; David J. Field; Craig N. Morrell (Immunologic Research, 2017)

Mixed-phenotype grouping: the interaction between oddity and crypsis - Gwendolen M. Rodgers; Helen Kimbell; Lesley J. Morrell (Oecologia, 2013)

Entorhinal cortex volume is associated with episodic memory related brain activation in normal aging and amnesic mild cognitive impairment - Mehul A. Trivedi; Travis R. Stoub; Christopher M. Murphy; Sarah George; Leyla deToledo-Morrell; Raj C. Shah; Susan Whitfield-Gabrieli; John D. E. Gabrieli; Glenn T. Stebbins (Brain Imaging and Behavior, 2011)

Effect of the adenosine A2A receptor antagonist MSX-3 on motivational disruptions of maternal behavior induced by dopamine antagonism in the early postpartum rat - Mariana Pereira; Andrew M. Farrar; Jörg Hockemeyer; Christa E. Müller; John D. Salamone; Joan I. Morrell (Psychopharmacology, 2011)

Compositional and transcriptional analyses of reduced zein kernels derived from the opaque2 mutation and RNAi suppression - Alessandra Frizzi; Rico A. Caldo; James A. Morrell; Meng Wang; Linda L. Lutfiyya; Wayne E. Brown; Thomas M. Malvar; Shihshieh Huang (Plant Molecular Biology, 2010)

RISK‐SENSITIVE ANTIPREDATOR BEHAVIOR IN THE TRINIDADIAN GUPPY, POECILIA RETICULATA - M. S. Botham; R. K. Hayward; L. J. Morrell; D. P. Croft; J. R. Ward; I. Ramnarine; J. Krause (Ecology, 2008)
The comparative approach has become a powerful tool for understanding how predation has shaped prey behavior. In this study we recorded the occurrence of common aquatic predator species and their densities in seven natural populations of Trinidadian guppies, Poecilia reticulata . We then exposed shoals of guppies from each of these populations to a series of predator treatments. Predator treatments differed in the species of predator used (pike cichlids, Crenicichla frenata ; rivulus, Rivulus hartii ; and freshwater prawns, Macrobrachium carcinus ) and thus in the level of risk posed. We recorded the antipredator responses of guppies in each of these predator treatments. The strength of antipredator behavior shown by guppies was affected by both the type of predator they were exposed to and the level of predation risk they experienced naturally in the wild. Importantly, we found that guppies from high‐risk populations showed a heightened response, compared to those from lower risk populations, only when exposed to the predator species that posed the greatest risk. Our results show the importance of individual predator species in shaping the behavioral traits of prey species at the population level. This has implications for prey movement between habitats that are geographically close but differ greatly in predator fauna.

Incentive salience of cocaine across the postpartum period of the female rat - Katharine M. Seip; Mariana Pereira; Michael P. Wansaw; Jenny I. Reiss; Eugenia I. Dziopa; Joan I. Morrell (Psychopharmacology, 2008)

Increasing the incentive salience of cocaine challenges preference for pup- over cocaine-associated stimuli during early postpartum: place preference and locomotor analyses in the lactating female rat - Katharine M. Seip; Joan I. Morrell (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

Crop‐to‐weed introgression has impacted allelic composition of johnsongrass populations with and without recent exposure to cultivated sorghum - P. L. MORRELL; T. D. WILLIAMS‐COPLIN; A. L. LATTU; J. E. BOWERS; J. M. CHANDLER; A. H. PATERSON (Molecular Ecology, 2005)
Sorghum halepense L. (johnsongrass) is one of the world's most noxious weeds, and a paradigm for the potential dangers of crop–weed hybridization. Introduced into the southeastern United States about 200 years ago, S. halepense is a close relative of cultivated sorghum ( Sorghum bicolor ). Both artificial crossing and experimental field studies have demonstrated the potential for S. halepense × S. bicolor hybrid formation, but no prior study has addressed the long‐term persistence of sorghum genes in johnsongrass populations. We surveyed 283 loci (on all 10 sorghum linkage groups) to identify 77 alleles at 69 loci that are found in US sorghum cultivars but are absent from a worldwide sampling of johnsongrass genotypes. These putatively cultivar‐specific alleles were present in up to 32.3% of individuals in johnsongrass populations adjacent to long‐term sorghum production fields in Texas and Nebraska. Lower frequencies of cultivar‐specific alleles at smaller numbers of loci are found in johnsongrass populations from New Jersey and Georgia with no recent exposure to cultivated sorghum, suggesting that introgressed sorghum alleles may be dispersed across long distances. The number of cultivar‐specific alleles and extensive multilocus patterns of cultivar‐specific allelic composition observed at both linked and unlinked loci in the johnsongrass populations, are inconsistent with alternatives to introgression such as convergence, or joint retention of ancestral polymorphisms. Naturalized johnsongrass populations appear to provide a conduit by which transgenes from sorghum could become widely disseminated.

Intercontinental dispersal: The origin of the widespread South American plant speciesGilia laciniata (Polemoniaceae) from a rare California and Oregon coastal endemic - P. L. Morrell; J. M. Porter; E. A. Friar (Plant Systematics and Evolution, 2000)